Fluid replacement protection of rabbits challenged subcutaneous with toxic shock syndrome toxins. - Lee, P K (1991)
Toxic shock syndrome toxin 1 (TSST-1) and streptococcal pyrogenic exotoxin A (SPE A) belong to a family of pyrogenic toxins produced by Staphylococcus aureus and Streptococcus pyogenes, respectively. Both toxins are responsible for causing toxic shock syndrome (TSS) and related illnesses, clinically characterized by multiorgan involvement. The most severe TSS symptom is acute hypotension and shock after the initial febrile response. In this study, we examined possible mechanisms of shock development in TSS, particularly the role of T-cell proliferation, endotoxin enhancement by toxins, and capillary leakage. American Dutch belted rabbits, with subcutaneously implanted miniosmotic pumps filled with either TSST-1 or SPE A, served as the animal model. For both TSST-1 and SPE A-treated rabbits, administration of cyclosporin A prevented toxin-induced T-cell proliferation but failed to protect the rabbits. Polymyxin B treatment of rabbits, to neutralize endogenous endotoxin, partially protected rabbits from challenge with either exotoxin; two of six rabbits survived on day 2 when treated with only TSST-1, whereas six of six animals survived after challenge with TSST-1 and polymyxin B. Similarly, with SPE A-treated rabbits, only 1 of 10 animals without polymyxin B treatment survived on day 8, but 4 of 6 rabbits survived on day 8 when given polymyxin B. Fluid replacement was successful in preventing lethality. Twelve of 14 rabbits survived when given TSST-1 with fluid, and all rabbits treated with SPE A and fluid survived. Finally, by using miniosmotic pumps, staphylococcal exfoliative toxin A and concanavalin A were administered to rabbits in an attempt to induce lethality. These two T-cell mitogens caused T-cell proliferation but failed to induce lethality in rabbits. The data suggest that toxin interactions causing vascular leakage and to some extent endotoxin enhancement are of major importance in development of hypotension and shock in TSS. It appears that T-cell proliferation may not contribute significantly to the induction of shock and death.